Incentive spirometry versus active cycle of breathing technique: effect on chest expansion and flow rates in post abdominal surgery patients - Wange, Pallavi; Jiandani, Mariya P.; Mehta, Amita (International Journal of Research in Medical Sciences, 2016)
Background: The patients undergoing abdominal surgery has characteristic post-operative mechanical abnormality in respiration like restrictive pattern of ventilation. Spontaneous deep breaths to restore functional residual capacity are abolished by pain. Incentive spirometry (IS) promotes frequent maximum inspiratory effort and is used for the prophylaxis and treatment of respiratory complications in post-surgery wards. Aim of the study was to compare the effect of incentive spirometry (IS) versus active cycle of breathing technique (ACBT) on flow rates and chest expansion in patients following abdominal surgery. Methods: It was prospective comparative interventional study. 90 patients posted for abdominal surgery and satisfying the inclusion criteria were included in the study. They were randomly divided through simple random sampling into two groups. Group A-IS group and Group B-ACBT group. Outcome measures were recorded as Peak inspiratory flow rate [PIFR], Peak expiratory flow rate [PEFR], Forced expiratory volume in 1 sec [FEV1] and chest expansion on pre and post-operative day five. Comparison of pre and post-operative day 1 and pre and post-operative day 5 was done using Wilcoxon signed Ranks Test for both group A and group B, further post hoc analysis was done by Tukey’s test at significance level of p<0.05. Inter as well as Intra group comparison was done. The comparison between group A and B for all the parameters was done by Mann- Whitney U test. At Statistical level of significance for Mann- Whitney U p<0.001. Results: Both IS and ACBT improve the peak flow rates and chest expansion in post abdominal surgery patients. Active cycle of breathing techniques is better technique compared to incentive spirometry in post abdominal surgery patients. Conclusions: ACBT (active cycle of breathing technique) has better results than incentive spirometry in post abdominal surgery cases.